An Investigation into Verbs in the Mental Process in "Truyen Kieu" by Nguyen Du and Their Translational equivalents in the english versions by michael counsell and Huynh Sanh Thong - Nguyễn Cao Thục Uyên (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aims to investigate verbs in mental process in “Truyen Kieu” by Nguyen and in their translational equivalents by Huynh and Counsell. Besides, it also points out the similarities and differences of translation strategies used in the two English versions compared to the original version. Additionally, this paper provides some practical suggestions about translation strategies used in translating verbs in mental process in literary works